Potential and limitations of methods for temperature uniformity mapping in high pressure thermal processing - Grauwet, Tara; Rauh, Cornelia; Van der Plancken, Iesel; Vervoort, Lisbeth; Hendrickx, Marc; Delgado, Antonio; van Loey, Ann (Trends in Food Science & Technology, 2012)
As pressure is assumed uniform and residence time is fixed, studying non-uniformity of high pressure process variables comes down to studying temperature uniformity. This review paper describes the progress made in developing two methods for temperature uniformity mapping within the EU FP6 integrated project: (i) computational thermal fluid dynamics (CTFD) modeling and simulation of temperature fields and (ii) use of pressure-temperature-time indicators (pTTIs) for experimental temperature uniformity mapping. In the first part of this contribution, the principle, potential and limitation of both procedures is outlined separately. In the second part, the outcome of the methods in the context of temperature uniformity illustration in different-scale high pressure reactors is exemplified and compared. Based on these examples, it is clear that the locations of low and high temperature zones depend on the pressure equipment used. Finally, screening literature data, some strategies are put forward to improve temperature uniformity under high pressure thermal processing conditions. © 2011 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.potent